Temperament and character in an Australian sample: examining cross-sectional associations of personality with age, sex, and satisfaction with life - Diann S. Eley; Vikas Bansal; C. Robert Cloninger; Janni Leung (PeerJ, 2023)
Objective Personality can influence how we interpret and react to our day-to-day life circumstances. Temperament and character are the primary dimensions of personality, and both are influenced genetically. Temperament represents our emotional core, while character reflects our goals and values as we develop through life. Research shows that where people live, their social, economic, and physical environment can influence attitudes and behaviors, and these have links to variations in personality traits. There are few studies that focus on Australian personality as temperament and character. Using an Australian general population sample, we examined the psychometric properties of the Temperament and Character Inventory (TCIR140) and investigated the associations between TCIR140 traits with both sociodemographic variables and measures of well-being. In addition, we investigated differences in temperament and character between our Australian general population sample and published results of similar studies from other countries. Methods Australians (N = 1,510) completed the Temperament and Character Inventory (TCIR-140), the Positive and Negative Affect Scale and the Satisfaction with Life Scale. Cronbach’s alpha and confirmatory factor analysis (CFA) examined the TCIR-140 psychometrics. Correlation analyzes, independent sample t-tests and ANOVA with post-hoc comparisons analyzed the sample. Results Cronbach’s alphas were high, ranging from α = 0.78–0.92, and the CFA confirmed two constructs of temperament and character. Females were higher in Harm Avoidance (p < 0.001), Reward Dependence (p < 0.001), and Cooperativeness (p < 0.001) compared to males, who were higher in Self-Directedness (p < 0.001). Age groups showed significant differences among all temperament and character traits (p < 0.001) except for Reward Dependence (p = 0.690). Young adults had the least resilient personality profile and poorest measures of well-being. Correlations with measures of temperament and character, well-being and affect were all in the expected direction. Conclusions Temperament and character are related to indicators of wellbeing and differs by age and sex. This Australian sample demonstrate a temperament that is high in Persistence and a character high in Self-Directedness and Cooperativeness with an overall postive affect and a general satisfaction with life. In comparison to other countries, Australians in this sample differ in levels of several traits, demonstrating a cautious and independent temperament with a character that is cooperative, industrious, and self-reliant. Young-adults in comparison to older groups have a temperament and character profile that is prone to negative emotions and a lower satisfaction with life.